Phylogeny of African fruit bats (Chiroptera, Pteropodidae) based on complete mitochondrial genomes - (:unkn) unknown (My University, 2020)
Members of the family Pteropodidae, also known as Old World fruit bats, are represented in Africa by 14 genera and 44 species. Here, we sequenced 67 complete mitochondrial genomes from African and Asian pteropodids to better understand the evolutionary history of the subfamily Rousettinae, which includes most of the African species. An increased frequency of guanine to adenine transitions is detected in the mtDNA genomes of Macroglossus sobrinus and all species of Casinycteris and Scotonycteris. Our phylogenetic and molecular dating analyses based on 126 taxa and 15,448 characters indicate a low signal for deep relationships within the family, suggesting a rapid diversification during the Late Oligocene period of “warming.” Within the subfamily Rousettinae, most nodes are highly supported by our different analyses (all nucleotide sites, SuperTRI analyses of a sliding window, transversions only, coding genes only, and amino acid sequences). The results indicate the existence of four tribes: Rousettini—distributed from Africa through Mediterranean region and South Asia to South-East Asia; Eonycterini—found in Asia; and Epomophorini and Scotonycterini—restricted to sub-Saharan Africa. Although most interspecies relationships are highly supported, three parts of the Rousettinae mitochondrial tree are still unresolved, suggesting rapid diversification: (a) among the three subtribes Epomophorina (Epomophorus sensu lato, i.e., including Micropteropus, Epomops, Hypsignathus, Nanonycteris), Plerotina (Plerotes), and Myonycterina (Myonycteris, Megaloglossus) in the Late Miocene; (b) among Epomops, Hypsignathus, and other species of Epomophorina at the Pliocene–Pleistocene boundary; and (c) among Myonycteris species in the Early Pleistocene. Within the Epomophorini, Stenonycteris lanosus emerged first, suggesting that lingual echolocation may have appeared in the common ancestor of Epomophorini and Rousettini. Our analyses suggest that multiple events
Keywords: African Research